MDMA-Induced Dissociative State not Mediated by the 5-HT2A Receptor - Drew J. Puxty; Johannes G. Ramaekers; Rafael de la Torre; Rafael de la Torre; Rafael de la Torre; Magí Farré; Magí Farré; Magí Farré; Neus Pizarro; Neus Pizarro; Mitona Pujadas; Mitona Pujadas; et al. (Frontiers Media S.A., 2017)
Previous research has shown that a single dose of MDMA induce a dissociative state, by elevating feelings of depersonalization and derealization. Typically, it is assumed that action on the 5-HT2A receptor is the mechanism underlying these psychedelic experiences. In addition, other studies have shown associations between dissociative states and biological parameters (heart rate, cortisol), which are elevated by MDMA. In order to investigate the role of the 5-HT2 receptor in the MDMA-induced dissociative state and the association with biological parameters, a placebo-controlled within-subject study was conducted including a single oral dose of MDMA (75 mg), combined with placebo or a single oral dose of the 5-HT2 receptor blocker ketanserin (40 mg). Twenty healthy recreational MDMA users filled out a dissociative states scale (CADSS) 90 min after treatments, which was preceded and followed by assessment of a number of biological parameters (cortisol levels, heart rate, MDMA blood concentrations). Findings showed that MDMA induced a dissociative state but this effect was not counteracted by pre-treatment with ketanserin. Heart rate was the only biological parameter that correlated with the MDMA-induced dissociative state, but an absence of correlation between these measures when participants were pretreated with ketanserin suggests an absence of directional effects of heart rate on dissociative state. It is suggested that the 5-HT2 receptor does not mediate the dissociative effects caused by a single dose of MDMA. Further research is needed to determine the exact neurobiology underlying this effect and whether these effects contribute to the therapeutic potential of MDMA.